2020
DOI: 10.1002/cbdv.202000710
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Identification of Pine Nut (Pinus yunnanensis Franch.) Protein Hydrolysate and Its Antioxidant Activity in Vitro and in Vivo

Abstract: In this study, the pine nut (Pinus yunnanensis Franch.) protein was hydrolyzed by alkaline protease and trypsin to prepare pine nut protein hydrolysate (PNPH). The chemical, intracellular and in vivo antioxidant capacity of PNPH were evaluated. PNPH owned the ability of scavenging free radicals, and it could protect the HepG2 cells from oxidative damage by preserving cell viability. Moreover, PNPH could reduce the malondialdehyde (MDA) content and improved the superoxide dismutase (SOD) and glutathione peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Moreover, there were 29 peptides which contained basic amino acid residues and 19 peptides which contained acidic amino acids ( Table 6 ). The acidic amino acids (Asp and Glu) and basic amino acids (His, Arg, and Lys) can quench unpaired electrons and radicals by using carbonyl and amino groups in the side chain as chelators of metal ions [ 94 ]. Liu et al reported that hazelnut-derived antioxidant peptide with an amino sequence of Asp-Trp-Asp-Pro-Lys involving two acidic amino acids, one basic amino acid, one aromatic amino acid, and two hydrophobic amino acids, possessed high ABTS and DPPH scavenging capacity [ 39 ].…”
Section: Structure-activity Relationship Of Antioxidant Peptidesmentioning
confidence: 99%
“…Moreover, there were 29 peptides which contained basic amino acid residues and 19 peptides which contained acidic amino acids ( Table 6 ). The acidic amino acids (Asp and Glu) and basic amino acids (His, Arg, and Lys) can quench unpaired electrons and radicals by using carbonyl and amino groups in the side chain as chelators of metal ions [ 94 ]. Liu et al reported that hazelnut-derived antioxidant peptide with an amino sequence of Asp-Trp-Asp-Pro-Lys involving two acidic amino acids, one basic amino acid, one aromatic amino acid, and two hydrophobic amino acids, possessed high ABTS and DPPH scavenging capacity [ 39 ].…”
Section: Structure-activity Relationship Of Antioxidant Peptidesmentioning
confidence: 99%
“…Pine nut meal is an agro‐industrial waste rich in protein remaining from the process of oil extraction. Pine nut protein hydrolysate (PNPH) has shown free radical scavenging activity, mitigating cell oxidative stress, along with a reduction in the lipid peroxidation and an increase in the SOD and GSH‐Px activities (Liu et al ., 2021).…”
Section: Antioxidant and Anticancer Activitiesmentioning
confidence: 99%
“…Two peptides, WSREEQEREE and ADIYTEEAGR, were found to retain the anti-photoaging properties of the walnut protein hydrolysates and they acted by downregulating gene expression of inflammatory cytokines (interleukins (IL)-1β and IL-6) and inhibiting MMP-1 activity and the phosphorylation of IκB and p-65 proteins, which are activators of the NF-κB/MMPs signaling pathway [ 83 ]. Similarly, pine nut-derived peptides (MQIFVK, MASVPTK, EMVELPLR and VVLIGDSGVGK) reduced D-galactose-induced premature aging in mice by suppressing lipid peroxidation and enhancing the activities of SOD and GPx in mouse serum, and heart and liver homogenates [ 84 ]. The ability to boost the activities of antioxidant enzymes (CAT, GSH, SOD and GPx) ( Figure 1 ), inhibit lipid peroxidation (malondialdehyde [MDA]) and protein oxidation (protein carbonyl), and downregulate gene expression of MMPs in mice have been reported as the antioxidant mechanisms of other FDAPs in preventing UV radiation-induced skin photoaging [ 83 , 85 , 86 , 87 ].…”
Section: Cellular Mechanisms Of Action Of Fdapsmentioning
confidence: 99%
“…The peptide also up-regulated gene expression of tumor suppressor gene (Bcl-2) and HO-1 via the PI3K/Akt/mTor//Nrf2/ARE pathway, and reduced oxidant-mediated ROS production in endothelial cells, leading to the amelioration of endothelial oxidative damage and atherogenesis in high fat fed ApoE-deficient mice ( Figure 1 ). Several other FDAPs (AYI, AYL, DREI, DREL, MQIFVK, MASVPTK, EMVELPLR, VVLIGDSGVGK and LEPVIGT) were recently demonstrated to protect HepG2 cells via the Keap1/Nrf2/ARE signaling pathway, leading to the upregulation of gene expression of antioxidant enzymes and ROS detoxification pathways [ 84 , 102 , 103 ]. Similar mechanisms were demonstrated by a dipeptide (IF) from potato protein hydrolysates in hypertension-generated ROS-induced renal damage in rats [ 104 ].…”
Section: Cellular Mechanisms Of Action Of Fdapsmentioning
confidence: 99%
See 1 more Smart Citation